The Transcription of the Correspondence between Leoš Janáček (1854-1928) and Emerik Beran (1868-1940) - Jernej Weiss (Muzikološki Zbornik, 2006)
Among the twenty-one preserved letters from Janáček to Beran, written during 1890 and 1928 in Czech, eight of Janáček’s letters and eight of Janáček’s postcards have been preserved, in addition to five official letters written during Beran’s pedagogical work at the Organ School in Brno. Among twenty-one of Beran’s letters to Janáček, written during 1914 and 1928 also in Czech, we can find eight of Beran’s letters and thirteen of Beran’s postcards, where in three of them, the place or time are not exactly given.